Pembuatan Film Pendek Bertemakan Persahabatan “How Bromance Us” - Willy Putranto Kurniawan; Vika Andriani; Tasha Rikayama (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2020)
A good relationship is not always shared by most teenagers especially in socializing, even not just teenagers, the bigger a person, the more difficult it will be for them to have sincere friendships. In the present era there are many bad things that cause a problem and also have a negative impact that starts from a friendship that is not good. According to an extreme statement by British anthropologist Robin Dunbar, we could have hundreds of friends, but no more than 5 could understand us. This statement and phenomenon is the inspiration for this short film work entitled "How Bromance Us". How Bromance Us is a short film with a fictional drama genre, this friendship has been going on for more than nine years, started from the thought of Edgar who strongly does not believe that there are friends in this world who are truly sincere in undergoing friendship. In one situation Edgar realized that what he always believed was the wrong thing because he realized that his little relative Ryan was a true friend because he had gone through good and bad things together and gave each other support to each other. This work uses steps for developing ideas, writing scripts, determining players, selecting sets and properties, reading, shooting and, and editing. The results of this work last 20 minutes accompanied by a moral message that being yourself is very important, but do not forget to keep the feelings of others, especially true friends. It is hoped that this non-thesis work can change the way the viewer views his friendship relationship and can inspire other filmmakers to continue producing works that have a strong moral message.